A Dopant‐Free Zwitterionic Conjugated Polyelectrolyte as a Hole‐Transporting and Interfacial Material for Perovskite Solar Cells. Issue 10 (11th August 2020) - Huan, Yihong; Tan, Chao; Wu, Bo; Feng, Xingcui; Xu, Wenting; Gao, Deqing
Abstract : Achieving rapid extraction and equivalent transport of charge carriers is an effective way to improve the performance of perovskite solar cells (PSCs). Herein, a thiophene‐based zwitterionic conjugated polyelectrolyte (poly(5‐amino‐5‐carboxy‐3‐oxapentyl)‐2, 5‐thiophene [POWT]) is introduced into PSCs as a hole‐transporting and interfacial material. The polyelectrolyte has a high hole mobility of 5.74 × 10 −3  cm 2  V −1  s −1 (similar to that of poly(triarylamine) [PTAA]) and compatible covalence level relative to the perovskite. Terminated with a zwitterionic pair of a ‐amino acid, POWT layer builds up a weak double‐layer capacitance at the interface, which is not strong enough to induce the migration of MA + ions in the perovskite layer. Deep electrical study on the PSC with the structure of indium tin oxide (ITO)/POWT/FA0.2 MA0.8 PbI2.9 Br0.1 /C60 /bathocuproine (BCP)/Ag discloses that the device has low carrier transfer resistance, low leakage current density, and minor interfacial charge accumulation. The open‐circuit voltage and the short‐circuit current density are much improved, and the power conversion efficiency (PCE) is up to 17.5%. With a ‐amino acid zwitterions, POWT passivates the surface charge defects and grain boundaries of the perovskite film. The PSC presents negligible hysteresis and high stability. After 56 days, the unencapsulated PSC still remains at 85% of the original efficiency. Abstract : A zwitterionic conjugated polyelectrolyte presents high hole mobility, compatible covalence level, and the ability for passivating surface defects of the perovskite film. The formation of a weak double‐layer capacitance, which is not strong enough to induce the migration of MA + ions, contributes to low carrier transport resistance and interfacial charge accumulation, leading to high efficiency and stability.